Hadzic's peripheral nerve blocks and anatomy for ultrasound-guided regional anesthesia - Hadzic, Admir (McGraw-Hill Professional, 2012)
"Hadzic's Peripheral Nerve Blocks delivers practical, state-of-the-art guidance for all major nerve block procedures, including ultrasound-guided nerve blocks. A standardized,user-friendly presentation provides meticulous, step-by-step instructions for each procedure. The second edition has been completely updated to include new developments, the latest equipment, and hundreds of new photographs"--Provided by publisher
Rev. ed. of: Peripheral nerve blocks : principles and practice. c2004
Keywords: Nerve block; Nerve Block -- methods; Peripheral Nerves -- anatomy & histology; Peripheral Nerves -- ultrasonography.; Ultrasonography -- methods